2007
DOI: 10.1007/s00270-007-9169-4
|View full text |Cite
|
Sign up to set email alerts
|

Local Therapeutic Results of Computed Tomography-Guided Transcatheter Arterial Chemoembolization for Hepatocellular Carcinoma: Results of 265 Tumors in 79 Patients

Abstract: Local therapeutic results of single new lesions were better than those of multiple new lesions, and the local therapeutic effect of TACE was not affected by the number of treatments on the basis of patient, tumor location, or tumor size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
0
15
1
Order By: Relevance
“…However, it was mostly used at a sub-subsegmental artery or a more distal artery. Third, the local tumor control rate was lower than that in previous reports (5,11,12). We think our TACE may be incomplete even though we could insert a microcatheter into a distal position.…”
Section: Discussioncontrasting
confidence: 58%
“…However, it was mostly used at a sub-subsegmental artery or a more distal artery. Third, the local tumor control rate was lower than that in previous reports (5,11,12). We think our TACE may be incomplete even though we could insert a microcatheter into a distal position.…”
Section: Discussioncontrasting
confidence: 58%
“…However, local control after TACE is inferior to that achieved after curative treatment. In a study of TACE involving 265 patients with HCC, the 3‐year local control rate for those who had tumors with complete and incomplete lipiodol accumulation was 41% and 9%, respectively . In addition, it has been reported that noncompact lipiodol accumulation after TACE is a risk factor for early local recurrence .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients with solitary HCC are not always suitable for these treatments, presumably because of poor liver function and/or tumor location. In such situations, the patient usually received transarterial chemoembolization (TACE); however, local control after TACE is unsatisfactory …”
Section: Introductionmentioning
confidence: 99%
“…In the same study, it was found that lesion morphology displayed significance for recurrence-free survival (p = 0.014%). Reported local recurrence rates for c-TACE at 1 and 3 years post baseline embolization include: 20 to 53.2% [43,44], 50.2 to 71.7% [43] for segmental embolizations that rise to 58 to 78% for nonsegmental embolization [43].…”
Section: Local Response Survival and Safety Profilementioning
confidence: 99%